Building the Croatian-English Parallel Corpus - Tadić, Marko (Array, 2000)
The contribution gives a survey of procedures and formats used in building the Croatian-English parallel corpus which is being collected in the Institute of Linguistics at the Philosophical Faculty, University of Zagreb. The primary text source is newspaper Croatia Weekly which has been published from the beginning of 1998 by HIKZ (Croatian Institute for Information and Culture). After quick survey of existing English-Croatian parallel corpora, the article copes with procedures involved in text conversion and text encoding, particularly the alignment. There are several recent suggestions for alignment encoding and they are elaborated. Preliminary statistics on numbers of S and W elements in each language is given at the end of the article.